Spiritual Benson Relaxation in Pre-Dialysis Chronic Kidney Failure Patients with Anxiety Problems: Case Study - Tata Mahyuvi; Dian Tukirahmawati (Chakra Brahmanda Lentera Institute, 2022)
Background: Chronic kidney failure patients say they are worried because they see the intervals flowing blood, costs incurred each time undergoing therapy, anxiety because invasive measures will be carried out, and uncertainty about recovery. This case study aims to carry out nursing care for patients with Pre-Dialysis Chronic Renal Failure Patients with anxiety nursing problems at Islamic Hospital Surabaya A.Yani. Methods: This type of research uses qualitative methods with a case study approach. The subjects were 1 Pre Dialysis Chronic Renal Failure patient with nursing problems for three interventions (1 time a day for 10-15 minutes) with data collection methods including assessment, determining diagnosis, making interventions, implementation, and evaluation. Results: Results of a case study of the Spiritual Application of Benson Relaxation in Pre-Dialysis Chronic Kidney Failure Patients at Rumah Sakit Islam Surabaya A.Yani with anxiety nursing problems three times. After carrying out nursing actions 3 x Pre-Hemodialysis Interventions in Chronic Kidney Failure patients, anxiety nursing problems can be resolved. Patients experience changes from initially having an Anxiety score of 78 (anxiety ) to 40 (not anxious). Conclusion: Therapy Spiritual Benson Relaxation effectively reduces anxiety, so it can be used as an alternative to reduce anxiety in patients with chronic kidney failure and for room nurses to be able to implement independent actions by implementing quick response actions so that patients can achieve optimal action.